Characterization and pathogenicity test of indigenous cellulolytic fungi as biofertilizer candidate. Issue 1 (April 2020) - Fikrinda, F; Susanna, S; Khalil, M; Sriwati, R; Syafruddin, S; Sufardi, S
Abstract: Cellulolytic fungi have an important role in regulating plant nutrition to sustain plant productivity. This study was aimed to characterize and test the pathogenicity of cellulolytic fungi isolated from the dry land of Aceh as a candidate for biofertilizer. A total of 30 isolates was characterized by their cellulolytic and phosphatase activity semi-quantitatively. The cellulolytic activities on amorph and crystalline cellulose were determined on the Mandel medium with CMC and Avicell as carbon sources respectively while phosphatase was observed on the Pikovskaya medium. The pathogenicity test of the potential isolates on maize, rice, and soybean was determined by the Knop's medium slants method. The results show that isolates with the ability to degrade amorph cellulose were more (93.33%) than crystalline (86.67%) and 80% isolates had activities on both cellulose types. Beside cellulolytic, most isolates (93.33 %) also had phosphatase activity. There were 23 isolates whose cellulolytic and phosphatase activities, five isolates were non-pathogenic on maize, rice, and soybean, two isolates on maize and rice, and one isolate on rice. These results indicate that the indigenous cellulolytic fungi from the dry land of Aceh were potential to be developed as biofertilizers in the cultivation of maize, rice, and/or soybean.